Did the Swiss exchange rate shock shock the market? - Manuel Buchholz; Gregor von Schweinitz; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
The Swiss National Bank abolished the exchange rate floor versus the Euro in January 2015. Based on a synthetic matching framework, we analyse the impact of this unexpected (and therefore exogenous) shock on the stock market. The results reveal a significant level shift (decline) in asset prices in Switzerland following the discontinuation of the minimum exchange rate. While adjustments in stock market returns were most pronounced directly after the news announcement, the variance was elevated for some weeks, indicating signs of increased uncertainty and potentially negative consequences for the real economy.
urn:nbn:de:gbv:3:2-92093
Keywords: C22; E50; F30; F41; 330; exchange rate shock; stock markets; uncertainty; synthetic matching